2014
DOI: 10.1021/jz5022087
|View full text |Cite
|
Sign up to set email alerts
|

Qualitatively Incorrect Features in the TDDFT Spectrum of Thiophene-Based Compounds

Abstract: Ab initio molecular electronic structure computations of thiophene-based compounds constitute an active field of research prompted by the growing interest in low-cost materials for organic electronic devices. In particular, the modeling of electronically excited states and other time-dependent phenomena has moved toward the description of more realistic albeit challenging systems. We demonstrate that due to its underlying approximations, time-dependent density functional theory predicts results that are qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
69
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 76 publications
(83 citation statements)
references
References 76 publications
14
69
0
Order By: Relevance
“…The spectra were decomposed into contributions from different states, S 1 (blue) and S 2 (red) for thiophene, S 1 (red) and S 3 + S 4 (blue) for bithiophene. The color code is consistent with the one used in our previous study, 23 and reflects the character of the pp* states. The energy windows used for the sampling of the initial conditions of the molecular dynamics simulations are also indicated.…”
Section: Vertical Excitation Energies and Spectramentioning
confidence: 63%
See 3 more Smart Citations
“…The spectra were decomposed into contributions from different states, S 1 (blue) and S 2 (red) for thiophene, S 1 (red) and S 3 + S 4 (blue) for bithiophene. The color code is consistent with the one used in our previous study, 23 and reflects the character of the pp* states. The energy windows used for the sampling of the initial conditions of the molecular dynamics simulations are also indicated.…”
Section: Vertical Excitation Energies and Spectramentioning
confidence: 63%
“…Achieving a balanced description of these states using electronic structure methods is not an easy task. In a recent letter 23 we showed that CIS (configuration interaction singles) and TDDFT invert ordering of the two pp* states. This is somewhat surprising for TDDFT, which is usually considered reliable for pp* states.…”
Section: Vertical Excitation Energies and Spectramentioning
confidence: 99%
See 2 more Smart Citations
“…The inversion of the L a and L b states was also spotted for 9H-adenine 35 by comparing TD-DFT estimates to high level reference values obtained with wave function-based approaches, such as EOM-CCSD(T) 36 (equation of motion-coupled cluster singles and doubles with perturbative triples) or CASPT2 37 (complete active space second-order perturbation theory), even though the ambiguity still remains in this case. 35 More recently, two of us have unraveled similar discrepancies for the low-lying ππ* states of thiophene and thienoacenes, 38 which constitute popular building blocks in organic electronics. Regardless of the exchange-correlation functional used, we found not only a spurious state inversion but also a wrong distribution of oscillator strengths and erroneous potential energy surfaces.…”
Section: Introductionmentioning
confidence: 97%